Clinicopathological and Prognostic Significance of Klotho and Estrogen Receptors Expression in Human Hepatocellular Carcinoma - Huang, Shu; Wang, Wei; Cheng, Yajun; Lin, Jie; Wang, Min (Turkish Journal of Gastroenterology, 2021)
Background: Hepatocellular carcinoma (HCC) is male-predominant cancer, but the underlying mechanism remains unclear. This studyaimed to investigate the expression of the age-suppressing gene klotho and estrogen receptors (ERs) in HCC patients and analyze theirassociation with clinicopathological variables and their effects on prognosis.Methods: The expression patterns of klotho, ERα, and ERβ were determined by tissue microarray and immunohistochemical technique,and their correlations with clinicopathological characteristics were investigated using univariate and multivariate analysis.Results: Klotho expression was significantly lower in HCC than in the adjacent noncancerous tissues (52.7% (49/93) vs. 90.8% (79/87),P = .000), and its protein level in HCC tissue was negatively correlated with clinical staging, histological grade, and stage of the primarytumor (T) (P < .05). Whereas the expression of nuclear ERα and ERβ was higher in HCC than their corresponding non-neoplastic tissues(55.9% (52/93) vs. 35.6% (31/87), P = .006; 59.1% (55/93) vs. 43.7% (38/87), P = .038), and the level of nuclear ERα and ERβ in HCCtissue was inversely correlated with T stage, tumor size, and clinical staging (P < .05). Correlation analysis showed the expression levelof klotho, which is positively correlated with that of nuclear ERα (r = 0.243, P = .019). Patients with klotho-positive tumors had longersurvival than those with klotho-negative tumors (P = .002). Cox proportional hazards model analysis demonstrated that positive expressionof klotho was an important factor indicating good prognosis (P = .003).Conclusion: Klotho, partially regulated by ERα-mediated estrogen pathway, acts as a tumor suppressor and might be a novel biomarkercandidate for predicting progression and prognosis in HCC patients.